2014
DOI: 10.1186/s12876-014-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of overt upper gastrointestinal bleeding in a low resource setting: a real world report from Nigeria

Abstract: BackgroundUpper gastrointestinal bleeding (UGIB) remains a common medical problem worldwide that has significant associated morbidity, mortality, and health care resource use. This study outlines the aetiology, clinical presentation, and treatment outcomes of patients with UGIB in a Nigerian low resource health facility.MethodsThis was a descriptive study of consecutive patients who underwent upper gastrointestinal (GI) endoscopy for upper GI bleeding in the endoscopy unit of the Obafemi Awolowo University Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
7
18
0
Order By: Relevance
“…Portal hypertension secondary to schistosomal fibrosis is still common in Kenya complicating into upper GI bleeding (9). Kayamba et al in a study on trends of upper GI endoscopy in Zambia, showed that Esophageal varices were the commonest finding in patients presenting with haematemesis, increasing by 14 % per decade in that patient group (19) Evolution from injection sclerotherapy to endoscopic variceal ligation is portrayed in our findings as well as other studies (12,20). All patients with esophageal varices underwent variceal band ligation.…”
Section: Discussionsupporting
confidence: 76%
“…Portal hypertension secondary to schistosomal fibrosis is still common in Kenya complicating into upper GI bleeding (9). Kayamba et al in a study on trends of upper GI endoscopy in Zambia, showed that Esophageal varices were the commonest finding in patients presenting with haematemesis, increasing by 14 % per decade in that patient group (19) Evolution from injection sclerotherapy to endoscopic variceal ligation is portrayed in our findings as well as other studies (12,20). All patients with esophageal varices underwent variceal band ligation.…”
Section: Discussionsupporting
confidence: 76%
“…It is not clear if the higher mortality seen in low and middle income countries (LIMC’s) is due to patient demographics, severity on presentation, etiology or compliance with care standards. Esophageal varices has been implicated as the most common cause of UGIB in several African studies [211]. Rather than being due to alcoholic liver disease as in high income countries (HIC’s), varices in sub-Saharan Africa result from Schistosoma-related portal hypertension [5, 8, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they stated missing data as a major limitation in their study. Other studies in similar resource setting have evaluated causes of GI bleeding (Alema, Martin, & Okello, 2012), (Alatise et al, 2014), (Harries & Wirima, 1989) and as such, it is not possible to compare our findings with theirs since we did not study etiology of the GI bleeding in our study. GI bleeding has been characterized better in high resource settings with incidence rates of 134 per 100,000 in the UK and being the most common cause of hospitalization due to gastrointestinal disease in the United States, accounts for more than 507,000 hospitalizations annually in the US (Peery et al, 2015).…”
Section: Discussionmentioning
confidence: 84%